MoleculARweb: A Web Site for Chemistry and Structural Biology Education through Interactive Augmented Reality out of the Box in Commodity Devices - Rodríguez, Fabio Cortés (2021)
Augmented/virtual realities (ARs/VRs) promise to revolutionize STEM education. However, most easy-to-use tools are limited to static visualizations, which limits the approachable content, whereas more interactive and dynamic alternatives require costly hardware, preventing large-scale use and evaluation of pedagogical effects. Here, we introduce https://MoleculARweb.epfl.ch, a free, open-source web site with interactive AR webpage-based apps that work out-of-the-box in laptops, tablets, and smartphones, where students and teachers can naturally handle virtual objects to explore molecular structure, reactivity, dynamics, and interactions, covering topics from inorganic, organic, and biological chemistry. With these web apps, teachers and science communicators can develop interactive material for their lessons and hands-on activities for their students and target public, in person or online, as we exemplify. Thousands of accesses to moleculARweb attest to the ease of use; teacher feedback attests to the utility in online teaching and homework during a pandemic; and in-class plus online surveys show that users find AR engaging and useful for teaching and learning chemistry. These observations support the potential of AR in future education and show the large impact that modern web technologies have in democratizing access to digital learning tools, providing the possibility to mass-test the pedagogical effect of these technologies in STEM education.